# 1. given the functions f(x) = 3x – 4 and g(x) = 4x + 10, find the value of x for which f(x) = g(x).

1. given the functions f(x) = 3x - 4 and g(x) = 4x + 10, find the value of x for which f(x) = g(x).
a. 2
b. -2
c.-6
d. -14

## This Post Has 10 Comments

1. naomijamieson88 says:

2. ashlynmartinezoz2eys says:

$f(x)+g(x)=-x+4$

Step-by-step explanation:

We have the functions, $f(x)=3x-2$ and $g(x)=6-4x$.

It is required to find the sum of these functions.

That is, $f(x)+g(x)$.

On substituting the functions, we get,

$f(x)+g(x)=(3x-2)+(6-4x)$

i.e. $f(x)+g(x)=(3x-4x)+(6-2)$

i.e. $f(x)+g(x)=-x+4$

Thus, the sum of the functions i.e. $f(x)+g(x)=-x+4$.

3. coolman5999alt says:

Step-by-step explanation:

We have given two functions.

f(x) = 3x-2

g(x) = 6-4x

We have to find the addition of given two functions.

f(x)+g(x) = ?

Putting given values in above equation, we have

f(x)+g(x) = (3x-2)+(6-4x)

f(x)+g(x) = 3x-2+6-4x

f(x)+g(x) = (3-4)x+(6-2)

f(x)+g(x) = (-1)x + (4)

f(x)+g(x) = -x +4 which is the answer.

4. noobieplayerxd says:

$f(x)+g(x)=3x-2+6-4x=-x+4$

5. dommalb says:

f(x) = 3x - 2, g(x) = 6 - 4x

f(x) + g(x) = (3x - 2) + (6 - 4x)

= 3x - 2 + 6 - 4x       combine like terms

= (3x - 4x) + (-2 + 6)

= -x + 4

6. powellmj9216 says:

Basically substitute f(x) and g(x) in

3x-2+6-4x

Then simplify

-x+4 = 4-x

7. granthazenp5e9mj says:

$f(x)+g(x)=3x-2+6-4x=-x+4$

8. juan01sebastian00 says:

hehee

Step-by-step explanation:

Idk

9. stevewu168168 says:

N0 (f o g) x = 3x.

Step-by-step explanation:

If they are inverses of each other the f o g will equal x.

f o g  =  2(3x +3/ (4x - 2)  + 3  /    4(3x + 3)/(4x - 2) - 3)

=  2(3x + 3)+ 3(4x - 2)                4x - 2

*

4x - 2                     4(3x + 3) - 3(4x - 2)

6x + 12x

=

12 - 6

= 3x.

So they are not inverses.

10. alyssa0888 says: